2022
DOI: 10.3390/nu14071504
|View full text |Cite|
|
Sign up to set email alerts
|

Vitamin K2 Modulates Mitochondrial Dysfunction Induced by 6-Hydroxydopamine in SH-SY5Y Cells via Mitochondrial Quality-Control Loop

Abstract: Vitamin K2, a natural fat-soluble vitamin, is a potent neuroprotective molecule, owing to its antioxidant effect, but its mechanism has not been fully elucidated. Therefore, we stimulated SH-SY5Y cells with 6-hydroxydopamine (6-OHDA) in a proper dose-dependent manner, followed by a treatment of vitamin K2. In the presence of 6-OHDA, cell viability was reduced, the mitochondrial membrane potential was decreased, and the accumulation of reactive oxygen species (ROS) was increased. Moreover, the treatment of 6-OH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…There is also evidence that VK2 supplementation reduces the diabetes development risk, as just 10 μg/day of VK2 can lower diabetes risk by 7% . In addition, numerous studies have demonstrated that VK2 possesses antioxidative and mitochondrial protective abilities. , It is inspiring that latest study reported vitamin K cycle as an effective ferroptosis suppressor . However, research studies have not well explained its potential actions between ferroptosis and T2DOP.…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that VK2 supplementation reduces the diabetes development risk, as just 10 μg/day of VK2 can lower diabetes risk by 7% . In addition, numerous studies have demonstrated that VK2 possesses antioxidative and mitochondrial protective abilities. , It is inspiring that latest study reported vitamin K cycle as an effective ferroptosis suppressor . However, research studies have not well explained its potential actions between ferroptosis and T2DOP.…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that treatment with VK2 improved the mitochondrial function, and increased the PINK1/Parkin signaling pathway of mitophagy, the fusion protein Mfn2, and mitochondrial biogenesis regulator PGC-1α expression. Previous studies have shown that VK2 could reinstate mitophagic activities by upregulating PINK1 and Parkin proteins [ 30 , 53 ]. Furthermore, as a mitochondrial electron carrier, VK2 could rescue PINK1-deficiency-induced mitochondrial dysfunction [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as a mitochondrial electron carrier, VK2 could rescue PINK1-deficiency-induced mitochondrial dysfunction [ 54 ]. Additionally, VK2 promoted mitochondrial fusion and biogenesis by increasing the expression of Mfn2 and PGC-1α [ 30 ]. Therefore, our results suggest that mitochondrial quality control may be an important mechanism for VK2 to improve mitochondrial function in ALI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has the function of protecting mitochondria when the cell has abnormally high energy requirements. When mitochondria are damaged, the cell recognizes and clears the dysfunctional mitochondria through the Pink1 protein (Vos et al, 2012 ) and/or mitochondrial quality‐control loop (Tang et al, 2022 ). It is now known that this steady‐state imbalance is related to the occurrence of Parkinson's disease (PD) (Opdebeeck et al, 2019 ).…”
Section: Biological Response To Vitamin K2: Main Findings and Discussionmentioning
confidence: 99%